Exploring building materials: human skin as a sensory reference in the absence of visual cues - Kudaligama, A.; Udawattha, C. (Frontiers in Built Environment, 2024)
Material texture significantly influences how people perceive built environments, yet empirical evidence supporting its impact on spaciousness perception is limited. This study aimed to explore how people perceive building materials through sense in the absence of visual attention and how texture meanings affect indoor spaciousness perception. Conducted with 160 participants (90 males, 70 females, mean age ±SD: 22 ± 5 years), the study comprised three phases: baseline tactile assessment, blindfolded navigation in a lab and exposure to real-world environments. Findings revealed the skin’s ability to discern textural quality without visual cues, with slightly rough wall surfaces consistently perceived as more spacious. Moreover, the association between wall texture and perceived space varied, with subjective aspects influencing spaciousness in relatively spacious rooms, while objective factors played a larger role in less spacious settings. This study provides insights into sensory referral processes, warranting further investigation into the potential psychological impacts of textures.